An EFL Students’ Perception Towards Game-Based Learning in Secondary School: A Descriptive Qualitative Study - Camelia Nur Jihan, Camelia Nur Jihan; Maharsi, Ista (UIR Press, 2024)
Game-based learning (GBL) is an innovative approach that involves students in identifying game elements that are relevant to the context set by the teacher. This method has proven to be effective and increasingly relevant in educational settings. This study aims to explore secondary EFL students' perceptions towards the use of Game-based learning (GBL) in secondary schools, using a descriptive qualitative research design. The main focus of this study was to investigate how Game-based learning (GBL) can effectively increase student engagement and motivation. The results showed that Game-based learning (GBL) not only serves as a learning support tool, but also promotes improved learning outcomes as well as develops students' adaptability. Based on these findings, some recommendations for the implementation of Game-based learning (GBL) in the context of secondary education are proposed, hoping to enrich future teaching strategies. This research contributes to a deeper understanding of the potential of Game-based learning (GBL) in education.